Mechanical Performance Test and Plastic Design Method Exploration of Narrow Width Steel Box Composite Beams - Yunteng Chen; Kaiqiang Qin; Yongchun Zhang; Zhenghua Li; Xiangsen Hu; Yawei Guo (Advances in Civil Engineering)
In order to study the negative stress performance of large-span and narrow-area steel box composite beams, a 1:4 large-scale experimental study was conducted. The load–displacement characteristics, cross-sectional strain distribution, and failure characteristics of the composite beams were analyzed and the model was subjected to finite element numerical simulation and theoretical calculation. The results showed that the steel beams in the negative moment zone of the narrow-area steel box composite beam were mainly marked by local buckling, large deformation of the web plates on both sides and plastic buckling failure at the variable cross section of the bottom plate. The steel box composite beam specimen is basically in the elastic development stage before buckling and the bending moment at which it reaches buckling is 84% of the ultimate bending moment (5052 kNm). Under the ultimate bending moment, the steel bars in the composite beam concrete slab enter the yield stage and the negative bending moment zone is mostly distributed with transverse cracks on the concrete surface, with the crack width within the range of 0.2 mm. The test value of bending bearing capacity is 1.41 times the calculated value in the bending bearing capacity specification (the steel strength is taken as the design value of 275 MPa), indicating that the narrow steel box composite beam can meet safety requirements and has a high safety factor. The test value of bending bearing capacity is 1.1 times the ultimate calculated value of bending bearing capacity (steel strength is taken as the standard value of 355 MPa), indicating that the narrow steel box composite beam undergoes overall yield failure, that is, the structure does not undergo local buckling failure before the steel reaches yield strength and has good stability. This further indicates that the narrow steel box composite beam still has good stability even in the simplified box structure. In addition, the plastic design of narrow steel box composite beams was discussed, a calculation method for plastic bending bearing capacity was proposed, and the rationality and safety of this calculation method were verified.